The Role of Madrasti Initiative in Developing Life Skills and Good Citizenship Values among the Students - Al-Makhariz, Lafi Saleh; Albado, Inas Ahmad; Atieh, Musa Ahmad (Dirasat: Educational Sciences, 2020)
The study aimed to invsetgate the role of the Madrasati initiative in developing life skills and test the impact of gender variables, experience and school level in the role of the initiative in the development of life skills and citizenship values in the schools of Mafraq Governorate. To achieve this aim a sample of random sample of 343 teachers was selected, and questionnaire was built. A questionnaire consisting of (25) items was prepared, divided into two areas: the role of the initiative in the development of life skills, where this area consists of (10) items and the role of the initiative in developing the values of citizenship where it consists of (15) items. After the tool was applied to the sample, the data were analyzed using the Statistical Package for the Social Sciences (SPSS) program. The results of the study showed that the role of the initiative was high both in terms of life skills development and in the development of the values of citizenship. The results also showed differences in the role of the initiative in developing life skills due to gender variables and school level, while there were no statistically significant differences in the role of the initiative in the development of good citizenship values due to gender variables, school level and experience.